(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, a fractional order nonlinear dynamic model of involving three person is introduced. The proposed model describes the dynamic behavior of an interrelation of three person under different structures. Stability analysis of the fractional-order nonlinear dynamic model of involving three person is studied using the fractional Routh-Hurwitz criteria. By using stability analysis on fractional order system, we obtain sufficient condition on the parameters for the locally asymptotically stable of equilibrium points. Finally, our results are validated by numerical simulations.